RE-ESTABLISHING ECOLOGICAL RELATIONS IN THE WORLDVIEW OF MENTAWAI INDIGENOUS RELIGION - Wahyuni, Dwi; Sabna, Anjali (Studia Sosia Religia, 2025)
Indigenous religion studies, particularly Arat Sabulungan in Mentawai, are dominated by the world religion paradigm, resulting in biased representations labeled "primitive," "animistic," or "syncretic." This paradigmatic bias not only hinders productive studies of indigenous religion but also obscures the ecological wisdom within their worldview. Amid the global ecological crisis, a new perspective on human-nature relations is needed, one that transcends the anthropocentric view that currently dominates religious discourse. This study aims to explore the worldview of the Mentawai indigenous religion regarding ecological relations and reconstruct ecological understanding from the perspective of the indigenous religion paradigm, specifically examining how rituals in Arat Sabulungan manifest the intersubjective relations between humans, nature, and spiritual entities. The study employs a humanistic approach, incorporating in-depth observations of Arat Sabulungan practices, with a focus on three main rituals: the sikerei healing ritual, the construction of uma, and the raising of pigs. Data are analyzed through the framework of the indigenous religion paradigm and the concept of worldview. Arat Sabulungan offers an understanding of intersubjective relations, different from the hierarchical relations of the world religion paradigm. Humans, nature, and spiritual entities are viewed as subjects possessing agency and consciousness. Healing rituals, the construction of uma, and the raising of pigs demonstrate a profound ecological awareness that manifests the reciprocal relationship between humans and nature. Epistemologically, this research offers an alternative paradigm for the study of indigenous religion. Theoretically, it enriches discussions of the role of religion in the ecological crisis by offering a cosmocentric perspective. Practically, the ecological awareness of Arat Sabulungan can inspire collective efforts to address the contemporary ecological crisis.